Influencers of Students’ English Language Speaking Proficiency: A Structural Equation Modeling Study - Hendriks, Anne Lou (LPPM Universitas Advent Indonesia, 2025)
The influence of the English language has increased the need for English language proficiency. Derived from the typical challenges to English language speaking proficiency (ELSP) of Indonesian students in West Indonesia, this study aimed to examine the relationships of the influencers of ELSP (motivation, language anxiety, environmental support, teachers’ communicative competence, assessment, and teaching strategies) to understand better the related problems in speaking English. It also sought the best predictive model of ELSP that may help English language learners in West Indonesia. After employing a postpositivist research paradigm, a correlational research design was used to obtain the perceptions of 251 simple randomly selected university students from West Indonesia. To gather data, 6 dependent variables were measured using 4 modified scales and 2 researcher-constructed scales. The students’ ELSP (dependent variable) was measured using their English Language 3 speaking scores. The final data analysis used Pearson’s r correlation and Structural Equation Modeling. Results revealed that none of the influencers had a significant correlation with ELSP. The data collected did not support the proposed conceptual framework and the theories used in this study. Such results find the need for alternative ways to enhance the ELSP of university students in West Indonesia. This study can be replicated with different samples to identify the causes of the mismatch of theories used in this study, since Indonesia has not officially accepted English as a second language.